(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The investigation of contemporary scenographic practices has provided an effervescent and complex arena for the creation, production, and theorization of artistic work, involving different disciplines, procedures, and ways of working that go beyond the very concept of scenography - including the direction and the dramaturgy itself. Among the numerous definitions of scenography today, we will investigate the concept of scenography in an expanded field as a starting point to discuss the term from a Southern, Latin American, and Brazilian perspective. We will analyze how expanded and site-specific practices have characterized a scenic writing identity from the South, using examples of works from the 1960s to the present, mainly in Sao Paulo.